The Impact of Digitalization on the Enterprise System: Russia and Italy and the Discipline of Smart Working Between Constraints and Opportunities - Egorova, Maria; D'Aponte, Marcello; Ponomareva, Daria; Minbaleev, Aleksei (LeXonomica, 2021)
The article is dedicated to the impact of digitalization on the enterprise system from the point of view of Italian and Russian legal regimes. The increasing impact of technological innovation in everyday life is leading to important changes, also in the context of the employment relationship, in many perspectives. The authors analyze the transformation of legal regulation of Italy and Russia in the sphere of labor relations, paying special attention to the challenges that occurred during the COVID-19 pandemic.Povzetek. Članek obravnava vpliv digitalizacije na podjetja z vidika italijanske in ruske pravne ureditve. Vse večji vpliv tehnoloških inovacij na vsakdanje življenje povzroča pomembne spremembe, tudi v okviru delovnih razmerij (z več različnih vidikov). Avtorji analizirajo preoblikovanje pravne ureditve Italije in Rusije na področju delovnih razmerij, pri čemer posebno pozornost namenjajo izzivom, ki so se pojavili med pandemijo COVID-19.